Relation between soil P test values and mobilization of dissolved and particulate P from the plough layer of typical Danish soils from a long‐term field experiment with applied P fertilizers. (4th July 2013) - Glæsner, N.; Kjaergaard, C.; Rubæk, G. H.; Magid, J.
Abstract Accumulation of phosphorus (P) in agricultural topsoils can contribute to leaching of P which may cause eutrophication of surface waters. An understanding of P mobilization processes in the plough layer is needed to improve agricultural management strategies. We compare leaching of total dissolved and particulate P through the plough layer of a typical Danish sandy loam soil subjected to three different P fertilizer regimes in a long‐term field experiment established in 1975. The leaching experiment used intact soil columns (20 cm diameter, 20 cm high) during unsaturated conditions. The three soils had small to moderate labile P contents, expressed by water‐extractable P (3.6–10.7 mg/kg), Olsen P (11–28 mg/kg) and degree of P saturation (DPS) (25–34%). Mobilization of total dissolved P (TDP) increased significantly (P < 0.05) from the intact soil columns with increasing labile P, whereas the increase in particulate P (PP) with increasing labile P content was modest and statistically insignificant. We found concentrations up to 1.5 mg TP/L for the plough layer of this typical Danish sandy loam soil. This highlights that even a moderate labile P content can be a potential source of TDP from the plough layer, and that a lower concentration margin of optimum agronomic P levels should be considered.